Kink Migration along 30° Si‐Core Partial Dislocations in 4H‐SiC. Issue 17 (21st April 2022) - Yakimov, Eugene E.; Yakimov, Eugene B.
Abstract : Single‐layer Shockley‐type stacking fault (SSF) expansion in 4H‐SiC due to irradiation by a focused e‐beam in the scan mode with a different rate and at fixed points has been studied. It is shown that the focused e‐beam enhances the 30° Si‐core partial dislocation glide at room and liquid nitrogen temperatures only at distances smaller than about 10 μm. The dislocations are found to glide as straight lines with a velocity independent of their length even when this length essentially exceeds the size of excitation volume and the diffusion length. The results obtained show that the dislocation velocity under irradiation is mainly determined by the double kink generation rate and allow to conclude that kink migration can occur without any excitation. The kink velocity in 4H‐SiC is estimated for the first time and the lower limit for the kink velocity is of 2 × 10 −4  cm s −1 at room temperature and about 2 times smaller at liquid nitrogen temperature that confirming the small activation energy for the kink migration in 4H‐SiC. Abstract : Irradiation of stacking faults in 4H‐SiC by e‐beam focused on the 30° Si‐core partial dislocations stimulates their glide as a line, which allows to assume very small activation energy for the kink migration.